2010
DOI: 10.1093/bioinformatics/btq126
|View full text |Cite
|
Sign up to set email alerts
|

PheWAS: demonstrating the feasibility of a phenome-wide scan to discover gene–disease associations

Abstract: Motivation: Emergence of genetic data coupled to longitudinal electronic medical records (EMRs) offers the possibility of phenome-wide association scans (PheWAS) for disease–gene associations. We propose a novel method to scan phenomic data for genetic associations using International Classification of Disease (ICD9) billing codes, which are available in most EMR systems. We have developed a code translation table to automatically define 776 different disease populations and their controls using prevalent ICD9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
1,067
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,044 publications
(1,078 citation statements)
references
References 21 publications
8
1,067
0
3
Order By: Relevance
“…Using automated phenotyping algorithms, investigators have identified cases and controls for diseases of interest to replicate known phenotype-genotype associations and make novel discoveries, [12][13][14][15][16][17] potentially with decreased cost 18 and faster execution than traditional trials.…”
Section: Background and Significancementioning
confidence: 99%
“…Using automated phenotyping algorithms, investigators have identified cases and controls for diseases of interest to replicate known phenotype-genotype associations and make novel discoveries, [12][13][14][15][16][17] potentially with decreased cost 18 and faster execution than traditional trials.…”
Section: Background and Significancementioning
confidence: 99%
“…For rare ICD9 codes where cell counts for a genotype fell below five in a contingency table, Fisher's exact test was used, similar to methods described in previous PheWASs. 4,6 Q-Q plots were generated for every SNP (data not shown) and at the study-wide level (Supplementary Material and Supplementary Figure S3) to measure systematic confounding or bias in the SNP-phenotype associations. The PheWAS results from the discovery set and validation set were combined by meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The common approach to account for multiple testing in PheWAS is the use of a Bonferroni correction. 1,4,6,[23][24][25] With 4841 phenotypes, 110 SNPs, and a studywide a of 0.05, an association with Po9.4 Â 10 À8 would be required to identify a statistically significant association assuming independence. The only association that meets this criterion is that between the PheWAS control SNP rs1061170 in CFH and ICD9 codes that define AMD (Figure 1e).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another major source of phenotyping data is the electronic health record (44,45). The breadth of these data presents both challenges and opportunities (46).…”
Section: Opportunities On the Horizonmentioning
confidence: 99%